Does Indigenous Knowledge Contribute towards the Benefits of Bioprospecting? - Pushpam Kumar Nori Tarui
This paper attempts to examine the contribution of indigenous and traditional knowledge in the process of bioprospecting, and propose a model to analyze how such knowledge influences the benefits of bioprospecting. Empirical evidence suggests that (i) out of the two widely debated but dissenting hypotheses on the benefits of bioprospecting, one estimating higher values is supported and (ii) if the bioprospecting search is based on ethno botanical information available from local people, then the value of bioprospecting benefits will be higher than those predicted by the two hypotheses. It is crucial for bioprospecting firms to design a scheme where the information as well as access to the resources can be effectively shared between the firms and the local people in the bioprospecting site.